2003
DOI: 10.1093/emboj/cdg380
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid lineage switch of Pax5 mutant but not wild-type B cell progenitors by C/EBP  and GATA factors

Abstract: The developmental potential of hematopoietic progenitors is restricted early on to either the erythromyeloid or lymphoid lineages. The broad developmental potential of Pax5−/− pro‐B cells is in apparent conflict with such a strict separation, although these progenitors realize the myeloid and erythroid potential with lower efficiency compared to the lymphoid cell fates. Here we demonstrate that ectopic expression of the transcription factors C/EBPα, GATA1, GATA2 and GATA3 strongly promoted in vitro macrophage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 68 publications
5
65
1
Order By: Relevance
“…In normal Blymphopoiesis, PAX5 accomplishes a dual function by activating Bcell commitment genes while concomitantly repressing non-B-lineage genes. PAX5 locks B-cell differentiation as PAX5-deficient cells are able to trans-differentiate in T and myeloid cells [122,123]. Furthermore Pax5 heterozygous mice show an accumulation of IL7-dependant proB cells and develop B-ALL when challenged by infections [124].…”
Section: Noncoding Mutations Affecting Pax5 Transcriptional Regulationmentioning
confidence: 99%
“…In normal Blymphopoiesis, PAX5 accomplishes a dual function by activating Bcell commitment genes while concomitantly repressing non-B-lineage genes. PAX5 locks B-cell differentiation as PAX5-deficient cells are able to trans-differentiate in T and myeloid cells [122,123]. Furthermore Pax5 heterozygous mice show an accumulation of IL7-dependant proB cells and develop B-ALL when challenged by infections [124].…”
Section: Noncoding Mutations Affecting Pax5 Transcriptional Regulationmentioning
confidence: 99%
“…The retrovirus M-Pax5-iCD2 as well as the parental virus MiCD2 (Heavey et al 2003) express a human CD2 indicator protein, which facilitated FACS sorting of the infected cells prior to PCR quantification of IgH rearrangements (Fig. 7A).…”
Section: Pax5 Induces Igh Locus Contraction and Distal V H -Dj H Rearmentioning
confidence: 99%
“…A human Pax5 cDNA was inserted upstream of the IRES-hCD2t gene of the retroviral vector MiCD2, which results in expression of a C-terminally truncated (t) human (h) CD2 indicator protein (Heavey et al 2003). The M-Pax5-iCD2 virus was generated and used for infection of Pax5 −/− and Pax5 −/− RAG2 −/− pro-B cells as described (Heavey et al 2003).…”
Section: Retroviral Infection Of Pro-b Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, although at a slightly lower level than in CLPs, C͞EBP␣ up-regulation was observed in IL-2R␤TG proB cells upon IL-2 stimulation in the same fashion as in IL-2R␤TG CLPs. Because it has been shown that the removal of Pax5 enables proB cells to differentiate into macrophages (22) in the presence of ectopic C͞EBP␣ (22,23), we hypothesized that Pax5 expression might be critically involved in this lineage conversion in proB cells from lymphoid to myeloid lineage. Therefore, we next examined Pax5 expression in IL-2R␤TG CLPs and proB cells after IL-2 stimulation.…”
Section: C͞ebp␣ Is a Major Component To Initiate Gm Differentiation Frommentioning
confidence: 99%